Tissue Factor–Factor VII Complex As a Key Regulator of Ovarian Cancer Phenotypes - Koizume, Shiro (Biomark Cancer, 2015)
Tissue factor (TF) is an integral membrane protein widely expressed in normal human cells. Blood coagulation factor VII (fVII) is a key enzyme in the extrinsic coagulation cascade that is predominantly secreted by hepatocytes and released into the bloodstream. The TF–fVII complex is aberrantly expressed on the surface of cancer cells, including ovarian cancer cells. This procoagulant complex can initiate intracellular signaling mechanisms, resulting in malignant phenotypes. Cancer tissues are chronically exposed to hypoxia. TF and fVII can be induced in response to hypoxia in ovarian cancer cells at the gene expression level, leading to the autonomous production of the TF–fVII complex. Here, we discuss the roles of the TF–fVII complex in the induction of malignant phenotypes in ovarian cancer cells. The hypoxic nature of ovarian cancer tissues and the roles of TF expression in endometriosis are discussed. Arguments will be extended to potential strategies to treat ovarian cancers based on our current knowledge of TF–fVII function.